miR-200a attenuated oxidative stress, inflammation, and apoptosis in dextran sulfate sodium-induced colitis through activation of Nrf2 - Peng, Shuai; Shen, Lei; Yu, Xiaoyun; Wu, Jing; Zha, Lanlan; Xia, Yuan; Luo, Hesheng (Frontiers in Immunology, 2023)
Oxidative stress and inflammatory responses are critical factors in ulcerative colitis disease pathogenesis. Nuclear factor erythroid 2-related factor 2 (Nrf2) modulates oxidative stress and suppresses inflammatory responses, and the protective benefits of Nrf2 activation have been associated with the therapy of ulcerative colitis. could target Kelch-like ECH-associated protein 1 (Keap1) and activate the Nrf2-regulated antioxidant pathway. Nevertheless, whether miR-200a modulates the Keap1/Nrf2 pathway in dextran sulfate sodium (DSS)-induced colonic damage is unknown. Here, our research intends to examine the impact of miR-200a in the model of DSS-induced colitis. Prior to DSS intervention, we overexpressed miR-200a in mice for four weeks using an adeno-associated viral (AAV) vector to address this problem. ELISA detected the concentration of inflammation-related cytokines. The genes involved in inflammatory reactions and oxidative stress were identified using quantitative reverse transcription-polymerase chain reaction (qRT-PCR), western blot, and immunofluorescence. Moreover, we applied siRNAs to weakened Nrf2 expression to confirm the hypothesis that miR-200a provided protection via Nrf2. The present study discovered miR-200a down-regulation, excessive inflammatory activation, enterocyte apoptosis, colonic dysfunction, and Keap1/Nrf2 antioxidant pathway inactivation in mouse colitis and NCM460 cells under DSS induction. However, our data demonstrated that miR-200a overexpression represses Keap1 and activates the Nrf2 antioxidant pathway, thereby alleviating these adverse alterations in animal and cellular models. Significantly, following Nrf2 deficiency, we failed to observe the protective benefits of miR-200a against colonic damage. Taken together, through activating the Keap1/Nrf2 signaling pathway, miR-200a protected against DSS-induced colonic damage. These studies offer an innovative therapeutic approach for ulcerative colitis.